ANTI-INFLAMMATORY PROPERTIES OF ZANTHOXYLUM OVALIFOLIUM WEIGHT METHANOLIC EXTRACT ON ALBINO WISTAR RATS - PAVANI P; RAJA NAIKA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The object of the present study, the methanolic leaf extract of Zanthoxylum ovalifolium was examined for anti-inflammatory activity and tested using carrageenan-induced paw edema in albino Wistar rats. Materials and Methods: The rats were grouped into five, each group consisting of six animals, Group I (negative control) received 1 ml of saline, Group II (standard) received 10 mg/kg p. o. of indomethacin, and remaining three groups received three different doses (100, 200, and 400 mg/kg p. o.) of the methanolic leaf extract after 1 h 0.1 ml of 1% carrageenan injection. The result of anti-inflammatory activity was set up to be dose-dependent in the carrageenan-induced paw edema model. Results: The methanolic leaf extract has shown significant (p<0.001) inhibition of paw edema, 66%, 66.03%, and 69.29% on the 3rd h at the doses of 100, 200, and 400 mg/kg, p. o., respectively. The results were expressed as the Mean±standard error of mean and statistical significance was analyzed by ANOVA followed by Dunnett’s test. The methanolic leaf of Z. ovalifolium extract showed significant anti-inflammatory activity compared with the standard drug indomethacin. Conclusion: Methanolic leaf extract of Z.ovalifolium showed excellent results in the anti-inflammatory experiment so, the plant can be explored as a potential medicine in suppressing inflammation.